2022
DOI: 10.29244/jcfcs.1.2.81-95
|View full text |Cite
|
Sign up to set email alerts
|

Job Motivation, Work-Family Conflict, and Job Satisfaction of Formal Working Mothers During Covid-19 Pandemic

Abstract: Work from home (WFH) policies can fade the boundaries between family and work matters, reduce work motivation, and create uncertainty that impacts job satisfaction. This study aims to analyze the effect of work motivation and work-family conflict on job satisfaction of formal working mothers during the Covid-19 pandemic. This study used a cross-sectional research design. The selection of research locations was chosen purposively, namely DKI Jakarta and West Java, because these two provinces were the two provin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…As such, the current findings shed a light on the importance of WFC and WFE in explaining the relationship between workers' motivations and WFB. Therefore, as predicted in the literature, the different types of workers' motivations will contribute to WFC and WFE perceptions (e.g., [25,28,34]). In turn, in line with the suggestion by Rothbard et al [1], WFC and WFE perceptions will contribute to shaping the individuals' perception of WFB.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As such, the current findings shed a light on the importance of WFC and WFE in explaining the relationship between workers' motivations and WFB. Therefore, as predicted in the literature, the different types of workers' motivations will contribute to WFC and WFE perceptions (e.g., [25,28,34]). In turn, in line with the suggestion by Rothbard et al [1], WFC and WFE perceptions will contribute to shaping the individuals' perception of WFB.…”
Section: Discussionmentioning
confidence: 97%
“…Kuvaas et al [27] also found a positive connection between extrinsic motivation and WFC and a negative relationship between intrinsic motivation and WFC. Additionally, Melati and Rizkillah [28] observed a negative and significant relationship between intrinsic motivation and WFC and identified motivation and WFC.…”
Section: The Relationship Between Workers' Motivation and Work-family...mentioning
confidence: 94%
See 1 more Smart Citation